Migration, Hybridity, and Identity in Salman Rushdie’s In the South - Pratiwi, Dyani Prades; Hawa, Andina Meutia; Iman, Diah Tyahaya; Nurhayati, Nurhayati; Ferdinal, Ferdinal (Andalas International Journal of Socio-Humanities, 2026)
Globalization has made migration a social phenomenon, with many people treating it as a life option without realizing the consequences. As a reflection of life, literature, especially migrant literature, can serve as a valuable source for studying this phenomenon. Salman Rushdie, a writer of migrant literature, raises the topic of migration in his work In the South. This study aims to examine how migration produces hybridity, liminality, and identity instability in the characters of the story. This study uses qualitative textual analysis of a literary work using Bhabha’s postcolonial theory of hybridity in analyzing the data. The study's results reveal that the characters in the story exist in an in-between space where identities are fluid, unstable, and continually reconstructed through cultural blending in new environments. The cultural blending that occurs during the migration process causes several impacts on the identities of these characters, all of which lead to the formation of a new identity. The hybrid characters in the story emerge as a source of tension, highlighting the complexities of migrant experience.